2004
DOI: 10.1152/ajpgi.00187.2004
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of NOS isoforms during experimental colitis: endothelial-derived NOS maintains mucosal integrity

Abstract: The role of nitric oxide (NO) in inflammatory bowel diseases has traditionally focused on the inducible form of NO synthase (iNOS). However, the constitutive endothelial (eNOS) and neuronal (nNOS) isoforms may also impact on colitis, either by contributing to the inflammation or by regulating mucosal integrity in response to noxious stimuli. To date, studies examining the roles of the NOS isoforms in experimental colitis have been conflicting, and the mechanisms by which these enzymes exert their effects remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 59 publications
0
45
1
4
Order By: Relevance
“…NO plays a crucial role in the gastrointestinal tract. 27) eNOS is an enzyme which mostly localizes to vascular endothelial cells and produces NO all the time. In a recent study, it was found that this enzyme is also expressed in gastrointestinal mucosal cells.…”
Section: Discussionmentioning
confidence: 99%
“…NO plays a crucial role in the gastrointestinal tract. 27) eNOS is an enzyme which mostly localizes to vascular endothelial cells and produces NO all the time. In a recent study, it was found that this enzyme is also expressed in gastrointestinal mucosal cells.…”
Section: Discussionmentioning
confidence: 99%
“…eNOS is a constitutive source of NO whereas iNOS is an inducible generator of NO during disease pathology (103,108,109). Genetic deletion of eNOS expression in the endothelium in the DSS and TNBS models resulted in increased disease activity, suggesting a protective role for eNOS derived NO acting in antioxidant, anti-inflammatory roles (132,133,161). Krieglstein et al (80,81) have also shown that loss of iNOS is protective in DSS colitis; they suggest that iNOSderived NO may be pathogenic and that tissue-derived iNOS makes a larger contribution to inflammatory cell recruitment than blood cell-derived iNOS.…”
Section: Angiogenic Mediators In Ibd and Experimental Colitismentioning
confidence: 99%
“…A béltraktusban mindhárom NOS izoforma megtalálható mind a kapillárisok endotéljében, a bélidegrendszer neuronjaiban és a bélfal izomzatában, azonban eloszlásuk, funkciójuk és aktivitásuk eltérő mértékben változik a fiziológiás és patológiás folyamatokban (Vannucchi, Corsani et al 2002, Vallance, Dijkstra et al 2004, Van Geldre, Fraeyman et al 2004, Talapka, Bodi et al 2011, Baccari, Traini et al 2012. Eddigi ismereteink alapján a konstitutív izoformáknak a bélrendszer fiziológiás állapotának fenntartásában betöltött szerepük, hogy szabályozzák az epitél réteg permeabilitását.…”
Section: Nos Izoformák a Béltraktusbanunclassified
“…dextrán szodium szulfát indukálta vastagbélgyulladásban nem mértek szignifikáns változást a nNOS mRNS-ének expressziójában, ugyanakkor a gyulladt területeken a nNOS fehérje nagyobb mennyiségben volt detektálható (Beck, Xavier et al 2004). Kísérletes vastagbélgyulladásban az eNOS fehérje mennyisége jelentősen megnő az endotél sejtekben (Beck, Xavier et al 2004, Vallance, Dijkstra et al 2004). Azért, hogy jobban megértsük, hogy az egyes izoformák milyen szerepet játszanak a gyulladás folyamatában, génmódosított egereken végeztek kísérleteket.…”
Section: Nos Izoformák a Béltraktusbanunclassified
See 1 more Smart Citation